2012
DOI: 10.1007/s13193-012-0173-z
|View full text |Cite
|
Sign up to set email alerts
|

Are We Over-treating Neck in Buccal & Alveolo-buccal Cancers: Experience from a Tertiary Cancer Care Center

Abstract: Oral cancer is one of the most common types of cancer seen in India with buccal and alveolo buccal regions being the most frequent subsites. A retrospective analysis of buccal and alveolo buccal cancer patients undergoing neck dissection from 1995 to 2009 was performed to analyze the profile of neck dissections and patterns of nodal involvement in these patients. Total 310 neck dissections were done for buccal and alveolo-buccal cancer including 41 (13.2 %) RND, 231(74.5 %) MND and 38 (12.2 %) Supraomohyoid ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 23 publications
1
24
1
Order By: Relevance
“…[23] and which was also focused by Dr. Deo (2012) on the data from the same centre[12]. In the present study, nodal involvement was found in 39.8% of the cases.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…[23] and which was also focused by Dr. Deo (2012) on the data from the same centre[12]. In the present study, nodal involvement was found in 39.8% of the cases.…”
supporting
confidence: 77%
“…Hence, along with treating the primary lesion, appropriate management of the cervical lymph nodes is an important part of oral cancer therapy [12] [19] [20] [21]. Also, there has long been controversy over the indication, timing and methods of neck dissection [20] [21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, the outcome of oral cancer may significantly change due to the nodal involvement. Hence, appropriate management of the cervical lymph nodes is an important part of oral cancer therapy [8][9][10][11][12][13]. However, there has been controversy over the indication, timing and methods of neck dissection [12,13].…”
Section: Introductionmentioning
confidence: 99%